Magnetic resonance fingerprinting – An overview. (September 2017) - Panda, Ananya; Mehta, Bhairav B.; Coppo, Simone; Jiang, Yun; Ma, Dan; Seiberlich, Nicole; Griswold, Mark A.; Gulani, Vikas
Abstract: Magnetic Resonance Fingerprinting (MRF) is a new approach to quantitative magnetic resonance imaging that allows simultaneous measurement of multiple tissue properties in a single, time-efficient acquisition. The ability to reproducibly and quantitatively measure tissue properties could enable more objective tissue diagnosis, comparisons of scans acquired at different locations and time points, longitudinal follow-up of individual patients and development of imaging biomarkers. This review provides a general overview of MRF technology, current preclinical and clinical applications and potential future directions. MRF has been initially evaluated in brain, prostate, liver, cardiac, musculoskeletal imaging, and measurement of perfusion and microvascular properties through MR vascular fingerprinting. Highlights: MRF is a new approach to quantitative MRI, allowing rapid and simultaneous measurements of multiple tissue properties. In MRF, MR system parameters are deliberately varied and each combination of property values produces a unique fingerprint . Signal evolution in each voxel is matched to the closest entry in dictionary of possible evolutions, yielding property maps. Some tissue properties measured include longitudinal and transverse relaxation times (T1, T2) and proton density (M0 ). Clinically MRF has been applied to multiple organs. MRF development, validation and applications are ongoing processes.